Impact of digital learning platforms on student performance: The role of digital literacy and user satisfaction - Poernomo, Moyo Hady; Budiwidjojo Putra, Alfa Santoso (Jurnal Mantik, 2024)
This study investigates the impact of digital learning platform utilization on student performance in higher education, considering the mediating roles of digital literacy and student satisfaction. The research employs a quantitative approach using survey methodology and path analysis to examine the direct and indirect relationships between variables. Data were collected from students using digital learning platforms and analyzed using Structural Equation Modeling (SEM) with Partial Least Squares (PLS) approach. The results reveal that digital learning platform utilization significantly influences student performance through both digital literacy and student satisfaction. Digital literacy emerged as a stronger mediator compared to student satisfaction, highlighting its crucial role in enhancing academic performance in the digital learning environment. Interestingly, the quality of instructor-student interaction did not significantly affect student performance through satisfaction. The study found that digital learning platform utilization strongly correlates with increased digital literacy and student satisfaction. Furthermore, digital literacy showed a moderate positive effect on student performance. These findings underscore the importance of fostering digital literacy skills and optimizing digital learning platforms to enhance student performance in higher education. The research provides valuable insights for educational institutions in developing effective digital learning strategies and emphasizes the need for comprehensive approaches in implementing digitall learning platforms